Comparison Of The Effect Of Social Background On The Wages Of Spanish Graduates Before And During A Crisis Context - Dani Torrents (GoAcademica Research & Publishing, 2023)
The economic context may have modified the relationship between higher education and the labour market. The rise in university fees, the labour market situation and the behaviour of employers, families and students could activate social background as a differentiating factor in post-higher education occupational status. The objective of the present study is to analyze if the social origin affects the labor insertion of the graduates, measured through their income. The labor insertion of graduates is analyzed in 2011 (crisis period) and compared with 2005 (period of economic expansion). Two Spanish databases are used in this analysis: the 2005 and 2011 Living Conditions Survey. The results presented show no income inequality related to social class of graduates. Between 2005 and 2011 most unskilled occupations suffered job destruction, thus homogenizing to some extent the graduates who were working in 2011 and reducing the internal differences.